Stakeholder perceptions of non-financial reporting (Department for Business, Energy and Industrial Strategy, 2019)
Non-financial reporting may include: a review of the company's business and the principal risks and uncertainties it faces, the company's corporate governance (for example diversity on boards), their environmental behaviours, corporate social responsibility. This research, commissioned by BEIS and conducted by PwC, examines stakeholder perceptions of regulations comprising the non-financial reporting regime in the UK. The report outlines the results of stakeholder interviews and a survey of companies to explore the impact of the regulations. It identifies: costs and benefits of the current regime, potential avenues for its development.
https://www.gov.uk/government/publications/non-financial-reporting-regime-stakeholder-perceptions
Keywords: Graue Literatur; Nachhaltigkeitsbericht; Stakeholder; Wahrnehmung; Großbritannien